Effect of core damage on elastic properties for time-lapse interpretation, offshore Brazil - Grochau, Marcos; Gurevich, Boris (University of Houston, 2007)
In order to calibrate time-lapse quantitative interpretation, it is crucial to analyze saturation and pressure effects on seismic velocities. While the former is adequately modeled using Gassmann, the latter is mainly obtained by laboratory measurements, which can be affected by core damage. Weinvestigate the magnitude of this effect on compressional wave velocities by comparing laboratory experiments and log measurements. We use Gassmann fluid substitution to obtain low-frequency saturated velocities from dry core measurements (thus mitigating the dispersion effects) taken at reservoir pressure. The analysis is performed for an unusual densely cored well from which 43 cores were extracted from a 45 meters thick turbidite reservoir. Comparison of these computed velocities with the sonic log measurements shows very good agreement. This confirms that for this particular region the effect of core damage on ultrasonic measurements is below the measurement error. Consequently stress sensitivity of elastic properties as obtained from ultrasonic measurements is adequate for quantitative interpretation of time-lapse seismic data.